Effectiveness of seasonal trivalent influenza vaccination against hospital-attended acute respiratory infections in pregnant women: A retrospective cohort study - Regan, Annette; de Klerk, N.; Moore, H.; Omer, S.; Shellam, G.; Effler, P. (Elsevier, 2016)
Background: Pregnant women are at risk of serious influenza infection. Although previous studies indicate maternal influenza vaccination can prevent hospitalisation in young infants, there is limited evidence of the effect in mothers. Methods: A cohort of 34,701 pregnant women delivering between 1 April 2012 and 31 December 2013 was created using birth records. Principal diagnosis codes from hospital emergency department (ED) and inpatient records were used to identify episodes of acute respiratory illness (ARI) during the 2012 and 2013 southern hemisphere influenza seasons. Cox regression models were used to calculate adjusted hazard ratios (aHRs) by maternal vaccination status, controlling for Indigenous status, socioeconomic level, medical conditions, and week of delivery. Results: 3,007 (8.7%) women received a seasonal influenza vaccine during pregnancy. Vaccinated women were less likely to visit an ED during pregnancy for an ARI (9.7 visits per 10,000 person-days vs. 35.5 visits per 10,000 person-days; aHR: 0.19, 95% CI: 0.05−0.68). Vaccinated women were also less likely to be hospitalised with an ARI compared to unvaccinated women (16.2 hospitalisations per 10,000 person-days vs. 34.0 hospitalisations per 10,000 person-days; aHR: 0.35, 95% CI: 0.13−0.97). Conclusions: Influenza vaccination during pregnancy was associated with significantly fewer hospital attendances for ARI in pregnant women.